2018
DOI: 10.1097/pgp.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Despite Diagnostic Morphology, Many Mixed Endometrial Carcinomas Show Unexpected Immunohistochemical Staining Patterns

Abstract: Historically, endometrial carcinomas have been classified primarily according to their histology. However, the use of immunohistochemistry has become commonplace in their evaluation, particularly in diagnostically challenging cases. Our objective was to evaluate mixed endometrial carcinomas using a well-established panel of biomarkers to assess the consistency and utility of these stains in clinical diagnosis. Eighteen cases comprised of various combinations of classical serous (SC), endometrioid (EC), and cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It is well known that the two types of tumors may have different pathogenesis, In clinical practice, mixed endometrial carcinomas exist in a considerable number of tumors, or due to the heterogeneity of tumors, the diagnosis of the same tumor tissue type and grade by pathologists may be out of sync, leading to challenges in the prognosis and treatment evaluation of patient. [13][14][15][16] A recent study performed an integrated genomic, transcriptomic and proteomic characterization of 373 endometrial carcinomas found that 25% of high-grade endometrioid tumors and uterine serous tumors had extensive copy number alterations and low ER/PR status. However, most endometrioid tumors have almost no copy number alterations, mainly manifested by gene stabilization and estrogen signaling activation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the two types of tumors may have different pathogenesis, In clinical practice, mixed endometrial carcinomas exist in a considerable number of tumors, or due to the heterogeneity of tumors, the diagnosis of the same tumor tissue type and grade by pathologists may be out of sync, leading to challenges in the prognosis and treatment evaluation of patient. [13][14][15][16] A recent study performed an integrated genomic, transcriptomic and proteomic characterization of 373 endometrial carcinomas found that 25% of high-grade endometrioid tumors and uterine serous tumors had extensive copy number alterations and low ER/PR status. However, most endometrioid tumors have almost no copy number alterations, mainly manifested by gene stabilization and estrogen signaling activation.…”
Section: Discussionmentioning
confidence: 99%
“…Roelofsen et al 14 showed that the prognosis for pure serous carcinomas was worse than for MECs. Matrai et al 22 immumohistochemically investigated 18 cases with MEC and they concluded that these tumors might not display the immunohistochemical prototype of their components and support for the complex evolution of mixed carcinomas. As a result of our study, we can say that, in the presence of more than 5% type 2 components, the prognosis is not different from those with pure type 2 endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Fadare et al 39 showed that a wild-type p53 staining result does not necessarily exclude SC in the correct clinical and morphologic setting and even demonstrated that such cases may still harbor pathogenic TP53 mutations. Matrai et al 40 demonstrated that in some cases of mixed SC/HGEC, the HGEC component can show a SC-like diffuse pattern of p16 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Fadare et al (39) showed that a wild-type p53 staining result does not necessarily exclude SC in the correct clinical and morphologic setting and even demonstrated that such cases may still harbor pathogenic TP53 mutations. Matrai et al (40) demonstrated that in some cases of mixed SC/HGEC, the HGEC component can show a SC-like diffuse pattern of p16 expression. We recommend that a completely negative (null) p16 staining result, in the presence of appropriately staining internal controls, when encountered in the setting of an otherwise classical clinicopathologic picture of SC (i.e.…”
mentioning
confidence: 99%